The new luxury equation: consumer values and market preferences - Nermain Al-Issa; Mohammad Abiad; Layal Kallach; Alice AlAkoum (Cogent Social Sciences)
This article identifies consumer segments based on their intentions to purchase different luxury products, categorized as functional and lifestyle luxury. Two studies compare them across countries distinct in their cultural and sustainable orientations. In the first study, respondents from Kuwait are clustered into functional luxury and lifestyle luxury consumers, with their motives compared across the identified segments. The second study applies the same methodology to respondents in the UK, resulting in similar consumer segments as those found in Kuwait. Logistic regression is then used to identify the motives for each segment and each country. This country-specific approach reduces potential biases from a one-size-fits-all methodology and helps identify distinct patterns and motivations unique to each cultural setting. The research suggests practical value-based positioning frameworks that can directly assist brand managers in making informed decisions about brand positioning and developing marketing strategies that effectively target the right segments. The current research fills a significant gap in the literature by introducing a novel approach to understanding the differences or similarities in the values consumers attach to various luxury categories across countries. This paper introduces the concept of perceived compatibility between luxury and sustainability as a novel component within consumer profiles.